Arabidopsis Carboxylesterase 20 Binds Strigolactone and Increases Branches and Tillers When Ectopically Expressed in Arabidopsis and Maize - Roesler, Keith; Lu, Cheng; Thomas, Jill; Xu, Qingzhang; Vance, Peter; Hou, Zhenglin; Williams, Robert W.; Liu, Lu; Owens, Michaela A.; Habben, Jeffrey E. (Frontiers in Plant Science, 2021)
Severe drought stress can delay maize silk emergence relative to the pollen shedding period, resulting in poor fertilization and reduced grain yield. Methods to minimize the delay in silking could thus improve yield stability. An Arabidopsis enhancer-tagged carboxylesterase 20 (AtCXE20) line was identified in a drought tolerance screen. Ectopic expression of AtCXE20 in Arabidopsis and maize resulted in phenotypes characteristic of strigolactone (SL)-deficient mutants, including increased branching and tillering, decreased plant height, delayed senescence, hyposensitivity to ethylene, and reduced flavonols. Maize silk growth was increased by AtCXE20 overexpression, and this phenotype was partially complemented by exogenous SL treatments. In drought conditions, the transgenic maize plants silked earlier than controls and had decreased anthesis-silking intervals. The purified recombinant AtCXE20 protein bound SL in vitro, as indicated by SL inhibiting AtCXE20 esterase activity and altering AtCXE20 intrinsic fluorescence. Homology modeling of the AtCXE20 3-D protein structure revealed a large hydrophobic binding pocket capable of accommodating, but not hydrolyzing SLs. The AtCXE20 protein concentration in transgenic maize tissues was determined by mass spectrometry to be in the micromolar range, well above known endogenous SL concentrations. These results best support a mechanism where ectopic expression of AtCXE20 with a strong promoter effectively lowers the concentration of free SL by sequestration. This study revealed an agriculturally important role for SL in maize silk growth and provided a new approach for altering SL levels in plants.